Semantics Issue: Emotive Meaning of Netizens’ Comments of Gastrointestinal Disease Survivors on Instagram @Kakagastro - Irawan, Yoga; Zalmansyah, Achril; Fitriani, Annisa (Universitas Muhammadiyah Kotabumi, 2024)
This study aims to describe the emotive meaning of netizens’ comments about survivors of gastrointestinal diseases on Instagram @kakagastro. This study uses a qualitative descriptive research method. The data in this study is in the form of screenshots in the form of comments written by followers of the @kakagastro account. The documentation method is used to obtain the data in the account. The data that has been obtained is then entered into the corpus of data that the researcher has previously designed. The results of the study show that three emotive meanings appear in the comments on the @kakagastro account. These emotive meanings, namely emotive meaning as an embodiment of worry, emotive meaning as an embodiment of social feelings, and emotive meaning as an embodiment of pleasure or happiness. The emotive meaning as a manifestation of worry comes from netizens who at that time were feeling anxious and afraid of the disease they were suffering from. This fear is manifested in the form of complaints and questions. The emotive meaning as a manifestation of social feeling comes from netizens' desire to consult about the illness they are suffering from. The consultation raises interaction and concern from the @kakagastro account with its followers. The emotive meaning of the embodiment of happiness is a meaning that arises because of the success of people with gastrointestinal diseases in consuming foods that should be prohibited. This success indicates that the healing process of gastrointestinal diseases is almost complete. Keywords: Instagram, emotive meaning, netizens